PEMBAHARUAN HUKUM TERHADAP PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA - Gusti Muhammad Reza; Meldianta Rahman; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The role of law is consistently required to anticipate all changes and developments that occur in society, one of which is regarding the rules for preventing violence in the home, with the deficiencies that occur in handling prevention of domestic violence when law enforcement is carried out, it is felt a legal renewal is needed against the provisions of the Law on Prevention of Domestic Violence. The issues raised are how legal reforms are needed in the Prevention of Domestic Violence and what are the obstacles faced in eradicating domestic violence. Legal renewal of the law formula on domestic violence requires careful consideration of the aspects of policy formulation and criminal aspects, which must receive special attention and improvement. And the obstacle that occurs is the thought that domestic violence cases are considered by society as a realm that other people should not interfere with, the Legalistic Paradigm of Law Enforcement Officials. The recommendation, in updating the law on the Law on Domestic Violence, must not ignore aspects related to human conditions, nature and Indonesian customs, while maintaining recognition of the laws that apply in society.Keywords: Law Renewal, Domestic Violence.